2012
DOI: 10.3892/or.2012.1940
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations of WWOX in Wilms’ tumor are involved in its carcinogenesis

Abstract: Loss of heterozygosity (LOH) in 16q appears in ~20-30% cases of Wilms' tumor. Within this region, known as common fragile site FRA16D, the WWOX tumor suppressor gene is located. Abnormalities of WWOX gene expression levels were observed in many tumor types and were associated with worse prognosis. The purpose of this study was to investigate the role of the WWOX tumor suppressor gene in Wilms' tumor samples. We evaluated the correlation between expression of WWOX and genes involved in proliferation (Ki67), apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
(37 reference statements)
1
31
0
Order By: Relevance
“…The WWOX gene has been identified as a candidate susceptible gene for many diseases by previous studies, in which several SNPs were reported to be associated with risk of multiple diseases, including lung cancer, gastric cancer, hypertension, wilms's tumor, breast cancer, thyroid carcinoma, ovarian cancer, myeloma and so on . In current study, we were the first to find evidence the WWOX gene deletion (CNV‐67048) was associated with increased risk of gliomas.…”
Section: Discussionmentioning
confidence: 56%
“…The WWOX gene has been identified as a candidate susceptible gene for many diseases by previous studies, in which several SNPs were reported to be associated with risk of multiple diseases, including lung cancer, gastric cancer, hypertension, wilms's tumor, breast cancer, thyroid carcinoma, ovarian cancer, myeloma and so on . In current study, we were the first to find evidence the WWOX gene deletion (CNV‐67048) was associated with increased risk of gliomas.…”
Section: Discussionmentioning
confidence: 56%
“…It has been confirmed to be altered in various types of cancer including breast, lung, gastric, ovarian, Wilms' tumor and glioblastoma multiforme (7)(8)(9)(10)(11)(12)(13). Genetic and epigenetic alterations of this gene include loss of heterozygosity (LOH) and promoter methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many molecules have been reported to be involved in the development and metastasis of prostate cancer including cyclin D1, retinoblastoma, p53 and WW domain-containing oxidoreductase (WWOX). 5 Several of these molecules tightly regulate the cell cycle, indicating that disorder of the cell cycle is an important event in prostate cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%